THE EFFECTIVENESS OF USING PODCASTS IN IMPROVING STUDENTS’ LISTENING SKILLS - Fitri Shofi Nur Iman; Siti Juliana Sari; Mida Maulida Rahmah; Naf’an Tarihoran (Jurnal Intelek Insan Cendikia, 2025)
The purpose of this study is to determine whether podcasts can help students who are learning English as a foreign language (EFL) improve their listening comprehension. From sources like ScienceDirect, PubMed, Mendeley, and Google Scholar, seventeen pertinent articles published between 2020 and 2025 were examined using a Systematic Literature Review (SLR) methodology supervised by PRISMA. The results show that both audio-only and video-based podcasts greatly improve a number of listening skills, including vocabulary recognition, pronunciation awareness, listening comprehension, and learner confidence. Students' hearing test scores significantly improved after being exposed to podcast-supported learning activities, according to the majority of experimental and quasi-experimental research.Podcasts, on the other hand, promote increased motivation, active involvement, decreased anxiety during listening tasks, and a more positive attitude toward digital learning settings, according to qualitative studies. The findings also emphasise how crucial it is to take into account instructional design, task alignment, accessibility, and material authenticity in order to optimise the efficacy of podcast integration.  Podcasts provide learners with flexible and relevant exposure to language use in everyday situations, enabling them to practice listening at any time and from any location, thereby promoting learning autonomy. In summary, podcasts have been shown to be a successful medium for contemporary listening teaching. This suggests that teachers should use podcasts in pre-, during-, and post-listening activities to encourage greater comprehension and autonomous learning in EFL classrooms.